Quality Dating: A Well-Defined Protocol Implemented at ETH for High-Precision 14C-Dates Tested on Late Glacial Wood. Issue 4 (18th August 2020) - Sookdeo, Adam; Kromer, Bernd; Büntgen, Ulf; Friedrich, Michael; Friedrich, Ronny; Helle, Gerhard; Pauly, Maren; Nievergelt, Daniel; Reinig, Frederick; Treydte, Kerstin; Synal, Hans-Arno; Wacker, Lukas
ABSTRACT: Advances in accelerator mass spectrometry have resulted in an unprecedented amount of new high-precision radiocarbon ( 14 C) -dates, some of which will redefine the international 14 C calibration curves (IntCal and SHCal). Often these datasets are unaccompanied by detailed quality insurances in place at the laboratory, questioning whether the 14 C structure is real, a result of a laboratory variation or measurement-scatter. A handful of intercomparison studies attempt to elucidate laboratory offsets but may fail to identify measurement-scatter and are often financially constrained. Here we introduce a protocol, called Quality Dating, implemented at ETH-Zürich to ensure reproducible and accurate high-precision 14 C-dates. The protocol highlights the importance of the continuous measurements and evaluation of blanks, standards, references and replicates. This protocol is tested on an absolutely dated German Late Glacial tree-ring chronology, part of which is intercompared with the Curt Engelhorn-Center for Archaeometry, Mannheim, Germany (CEZA). The combined dataset contains 170 highly resolved, highly precise 14 C-dates that supplement three decadal dates spanning 280 cal. years in IntCal, and provides detailed 14 C structure for this interval.